Development of crispy-sweet pickled radish products by vacuum frying and water pretreatment - Punyanunt, Sawanya; Ninchan, Boontiwa; Sithisam-ang, Damrongchai; Chalermsanyakon, Wannarat; Phakthanakanok, Krongsakda (Asia-Pacific Journal of Science and Technology, 2025)
Sweet pickled radish (Huah Chai Bpoh in Thai), which is a famous fermented food in Thailand, is made from white radish (Raphanus sativus L.). To add to its value, sweet pickled radish is processed by vacuum frying to produce a ready-to-eat snack. Water pretreatment was introduced to improve the quality of the sweet pickled radish product. The mass ratios for the pretreatment of sweet pickled radish to tap water were 1:3, 1:6, and 1:9. Then, it was fried at temperatures of 85, 90, and 95°C for 60, 90, and 100 min under vacuum conditions. The product quality parameters such as average diameter, visual appearance, color, and textural characteristics were examined. The results found that water pretreatment also decreased the total soluble solid content (TSS, °Brix) in the pickled radish sample, and the lowest TSS was observed at a ratio of 1:9. Such a pretreatment ratio induced the highest average diameter of fried product because the losing cellular structure strength after pretreatment promoted larger volume expansion during vacuum frying. Vacuum frying conditions comprising a temperature of 85°C for 100 min exhibited less browning and produced the highest hard texture. Moreover, Scanning electron microscopy (SEM) images of the fried product were different from fresh sweet pickled radish, as observed by larger pore sizes contained inside the fried product structures.